Psychometric testing of a set of patient-reported instruments to assess healthcare interventions for autistic adults. (April 2021) - Nicolaidis, Christina; Zhen, Kelly Y; Lee, Junghee; Raymaker, Dora M; Kapp, Steven K; Croen, Lisa A; Urbanowicz, Anna; Maslak, Joelle; Scharer, Mirah
There is a growing recognition of the need for interventions to improve the healthcare of autistic adults. However, there is a dearth of validated measures to evaluate such interventions. Our objectives were to use a community-based participatory research approach to create an accessible set of patient- and proxy-reported instruments to measure healthcare outcomes and potential intervention targets in autistic adults and to assess the instruments' psychometric characteristics, including content validity, construct validity, and internal consistency reliability. We administered a survey to 244 autistic adults recruited from 12 primary care clinics in Oregon and California, USA (194 participating directly and 50 participating via a proxy reporter). Community partners ensured items were easy to understand and captured the intended construct. The Academic Autism Spectrum Partnership in Research and Education (AASPIRE) Visit Preparedness Scale, Healthcare Accommodations Scale, and Patient–Provider Communication Scale were each found to have a single factor. The AASPIRE Health and Healthcare Self-Efficacy Scale had two factors: Individual Healthcare Self-Efficacy and Relationship-Dependent Healthcare Self-Efficacy. Both patient- and proxy-reported versions of all scales had good to excellent internal consistency reliability, with alphas ranging from 0.81 to 0.96. The scales were associated with the Barriers to Healthcare Checklist and the Unmet Healthcare Needs Checklist in the hypothesized directions. Lay Abstract: Interventions to improve healthcare for autistic adults are greatly needed. To evaluate such interventions, researchers often use surveys to collect data from autistic adults (or sometimes, their supporters), but few survey measures have been tested for use with autistic adults. Our objective was to create and test a set of patient- or proxy-reported survey measures for use in studies that evaluate healthcare interventions. We used a community-based participatory research (CBPR) approach, in partnership with autistic adults, healthcare providers, and supporters. We worked together to create or adapt survey measures. Three survey measures focus on things that interventions may try to change directly: (1) how prepared patients are for visits; (2) how confident they feel in managing their health and healthcare; and (3) how well the healthcare system is making the accommodations patients feel they need. The other measures focus on the outcomes that interventions may hope to achieve: (4) improved patient–provider communication; (5) reduced barriers to care; and (6) reduced unmet healthcare needs. We then tested these measures in a survey of 244 autistic adults recruited from 12 primary care clinics in Oregon and California, USA (with 194 participating directly and 50 participating via a proxy reporter). Community partners made sure items were easy to understand and captured what was important about the underlying idea. We found the survey measures worked well in this sample. These measures may help researchers evaluate new healthcare interventions. Future research needs to assess whether interventions improve healthcare outcomes in autistic adults.